2008
DOI: 10.1093/jat/32.8.594
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Glucuronide Excretion in Humans Following Oral Administration of and Dermal Exposure to Ethanol

Abstract: Ethyl glucuronide (EtG) is a direct ethanol biomarker and U.S. Department of Health and Human Services has advised that specificity studies at low EtG levels are needed for distinction of ethanol consumption and incidental exposure. The authors report urinary EtG excretion with ethanol abstinence, dermal exposure and oral consumption. EtG concentration by sensitive liquid chromatography-tandem mass spectrometry measurement in 39 urine specimens from adult alcohol abstainers (< 10-62 microg/L) and in urine from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…In humans, this should be studied by administering different doses and collecting all urine voided until the end of EtG elimination. One study administered 3-25 g of ethanol to 4 subjects, and showed a dose-response relationship, with a larger % of the ethanol excreted as EtG at higher doses (56). When comparing this to our results (paper IV) and those by Dahl et al (49), where larger doses were ingested, this further strengthens the picture of a dose-response curve.…”
Section: Blood Kinetics Of Etg and Ets In Living Subjectssupporting
confidence: 89%
See 1 more Smart Citation
“…In humans, this should be studied by administering different doses and collecting all urine voided until the end of EtG elimination. One study administered 3-25 g of ethanol to 4 subjects, and showed a dose-response relationship, with a larger % of the ethanol excreted as EtG at higher doses (56). When comparing this to our results (paper IV) and those by Dahl et al (49), where larger doses were ingested, this further strengthens the picture of a dose-response curve.…”
Section: Blood Kinetics Of Etg and Ets In Living Subjectssupporting
confidence: 89%
“…ADH is saturated at approximately 0.2 g/L ethanol, and this is in accordance with the findings of glucuronidation, which showed increasing activity after ingestion of doses higher than 0.15 g/kg, resulting in blood alcohol concentrations around 0.2 g/L (56). An alternative explanation is the lower bioavailability of ethanol when ingested in low doses.…”
Section: Blood Kinetics Of Etg and Ets In Living Subjectssupporting
confidence: 88%
“…However, in order to avoid false-positive results such as those obtained with a metabolite of chloral hydrate [25], the confirmation of EtG-positive results should be confirmed with another method. Furthermore, for the analysis of EtG in urine, true false-positive results of EtG were demonstrated in urine after use of mouthwash [18] and contact with hand sanitizer [28,42] containing ethanol. With the 13 blank serum samples mentioned above, EtG was not detected by CZE, and EIA provided very low EtG levels.…”
Section: Determination Of Etg In Real Samples By Cze and Eiamentioning
confidence: 99%
“…For doctors to understand UDT ethanol results, it is essential that they understand ethanol metabolism and the formation of the ethanol byproducts ethyl glucuronide and ethyl sulfate Crews et al, 2011b;Dahl et al, 2002;Helander & Beck, 2005;Helander et al, 1996;Rosano & Lin, 2008;Schmitt et al, 1997;Stephanson et al, 2002;Wojcik & Hawthorne, 2007;Wurst et al, 2006;Wurst et al, 2004). This is because false positive ethanol results can result from fermentation of glucose from diabetic patient samples .…”
Section: Monitoring Ethanol Use In Pain Patientsmentioning
confidence: 99%